GPS boundary navigation of DrosoBots using MATLAB simulation - Zainal Abidin, Zulkifli; Ngah , Vmi Kalthum; Arshad, Mohd Rizal; Kok , Chee Hou (2010)
This paper presents the initial developmental stage of mini Autonomous Surface Vehicles (ASVs), which is to define the algorithm of boundary navigation for each of the ASV via programming and sensor networks. To implement this, region recognition and several path planning algorithms have been utilized. Besides that, pixilation of path is also used to estimate the coverage of the path planning. The results from the experiment show that the Levy flight algorithm is more suitable to be used compared to normal random.